The community s hand on the wheel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The article in Spore 90 on irrigation management and 'Whose hand on the wheel?' rang more than a few bells with Beruk Kabtamu, planning and monitoring officer of the Lutheran World Federation s programme in Ethiopia. As well as reproducing the...